Foreign currency invoicing of domestic transactions as a hedging strategy: Evidence for Uruguay - Gerardo Licandro Ferrando; Miguel Mello Costa (Journal of Applied Economics, 2019)
This study is an empirical analysis of the factors associated with the use of the US dollar for the invoicing of domestic transactions, which is a common practice of Uruguayan firms. Using a novel dataset we find that both the input and debt structure of firms are relevant for determining their currency of invoicing. Intuitively, firms will generate cash flows in US dollar if they have to make expenditures in foreign currency, either because they use imported inputs or if they cover debt services with currency risk. This practice can be seen as a hedging strategy to mitigate exchange risk in a highly dollarized economy. We empirically show that firms use their flows position to hedge currency mismatches in their stocks; domestic invoicing in US dollar is correlated with large negative financial positions, and the share of imported inputs and of exports.
Keywords: 330; Currency invoicing; Dollarization; Exchange Rate Risk; Hedging